Status migrainosus inpatient treatment with eptinezumab (SMITE): study protocol for a randomised controlled trial. Issue 3 (8th March 2022) - Ray, Jason Charles; Chen, Zhibin; Ramsay, Georgia; Germaine, Jack; Hutton, Elspeth J
Abstract : Introduction: Status migrainosus is a disabling complication of migraine, which frequently results in hospitalisation. For patients who fail to respond to simple analgesia, triptans and intravenous prochlorperazine or chlorpromazine, there are limited treatment options, and a paucity of high-quality evidence to guide clinical practice. Eptinezumab, an intravenous monoclonal antibody specific for the calcitonin gene-related peptide ligand which achieves maximal plasma concentration immediately following administration and may improve migraines from day one. Intravenous lignocaine is an anaesthetic medication used in treatment of status migrainosus, often requiring prolonged admissions and with potential cardiac adverse events. The aim of this study is to assess the efficacy and safety of eptinezumab in the treatment of status migrainosus in comparison to intravenous lidocaine. Methods and analysis: Status migrainosus inpatient treatment with eptinezumab is a randomised, controlled, single-centre clinical trial conducted in a parallel design with an active comparator conducted in Melbourne, Australia. This study randomises forty patients (1:1) to receive either eptinezumab or an infusion of intravenous lignocaine for up to 5 days. It will assess the effect of eptinezumab compared with intravenous lignocaine in aborting status migrainosus, with the primary outcome of time from infusion until resolution of pain. It will explore several secondary measures including change in health resource utilisation, effect on patient reported outcomes of migraine disability and the safety and tolerability of each medication. Ethics and dissemination: This study has been reviewed and approved by the Human Research Ethics Committee of Alfred Health, local reference number 443/21, and all participants will provide informed consent for participation in the trial and dissemination of results. Trial registration number: The trial registration number is ACTRN12621001616864. The results of this study will be disseminated through peer-reviewed journals, conference presentations and social media.